Bridging the gap between paediatric to adult care: experiences with the transition of adolescents with chronic conditions in the Netherlands - van Staa, AnneLoes (Igitur, Utrecht Publishing & Archiving, 2009)
INTRODUCTION: Despite growing numbers of adolescents with chronic conditions, transition from paediatric to adult care has received little attention in the Netherlands. AIM: To identify gaps in transition to adult care of chronically ill adolescents from the perspectives of youth, parents and caregivers. METHODS: Semi-structured interviews with 24 adolescents (aged 15–22, with various chronic conditions), 24 parents and 17 healthcare professionals. Thematic analysis was performed using ATLAS.ti. RESULTS: Several themes were identified among adolescents and parents. Both viewed leaving paediatric care as a ‘logical step’, but noticed they were ‘unprepared and uninvolved’ in the process. Most parents found it ‘hard to leave familiar surroundings’, while adolescents' most common attitude was ‘wait and see’ reflecting a certain ease with the situation. However, both reported ‘feeling lost after transition’ due to cultural and procedural differences between paediatric and adult care. Adolescents are ‘struggling with responsibility’ in the adult environment, while parents find it hard ‘to let go in confidence’. One overarching theme, ‘gaining trust’, appeared from caregivers, adolescents, and parents. CONCLUSION: Adolescents' preparation for adult care is deficient from patient, parent and caregiver perspectives. Transitional care should focus on adolescents' independency, parental involvement and bridging the gap between paediatric and adult caregivers.